"Mother of Twenty-one" primary and elementary teachers' workloads and health in rural and urban Newfoundland and Labrador - Temple, Julia R., 1979 (2009)
Thesis (Ph.D.)--Memorial University of Newfoundland, 2009. Sociology Includes bibliographical references (leaves 245-260) Research has shown that many primary and elementary teachers in Newfoundland and Labrador and elsewhere struggle with heavy workloads (Dibbon, 2004; Schaefer, 2003) that can impact their health and well-being (Messing, Seifert, and Escalona, 1997; Younghusband, 2005). Teachers' workloads are strongly shaped by gender (Acker, 1996) and place, including rural and urban contexts. However, most research on teacher workload has an urban focus, with little rural-urban comparison (Abel and Sewell, 1999). -- The purpose of this study was to examine primary and elementary teachers' workloads and health in rural and urban areas of Newfoundland and Labrador. I was guided by a theoretical framework based on a social determinants of health approach, and focusing on the importance of gender and place as determinants of health. -- My methodological approach is a feminist action research framework that divided the research into advisory, research, and feedback stages, and included writing a report for the provincial teachers' union. I conducted individual interviews with twenty-four primary and elementary teachers and six representatives of other groups in education, including parents, administrators, student assistants, the teachers' union, school boards, and the Department of Education. I also had the participating teachers complete detailed one-day task-diaries, which we then discussed in the interviews. I questioned participants on their perceptions of primary and elementary teachers' teaching and domestic workloads, the consequences of this work for their health and well-being, and their suggestions for how these workloads can be improved. Participants were invited to offer feedback on the summary report, which was incorporated into the report and this thesis. -- The teachers in this study identified five main areas of concern related to their teaching workloads: the intense and all-consuming nature of their work; emotional labour; specific tasks such as supervision duty, paperwork, planning, preparation and correcting, student evaluations, and implementing the 'Pathways' program; lack of human and material resources; and a persistent sense of invisibility. In addition, I found that teachers, particularly those with young children, were struggling to balance their teaching and domestic work. Years of experience, rural or urban location, and gender were all important factors affecting these workloads. In fact, I describe primary and elementary teaching as a "mothering profession" to reflect the way that this work is gendered so strongly around mothering. Teachers also raised a number of concerns about the effects of their workloads on their families' well-being as well as their own. These concerns included tiredness; guilt; feeling overwhelmed, rushed, or stressed; lack of time for themselves; physiological problems, such as headaches, voice problems, and lower limb pain; and difficulty taking time off when ill. Based on this research, I discuss the need for a wider understanding of the concept of well-being that takes into account teachers' and women's "ordinary suffering." Finally, I discuss teaching as a profession, and show how the changes in teachers' work reveals important insights about the relationship between gender and professional work.